2018
DOI: 10.1038/s41586-018-0416-4
|View full text |Cite
|
Sign up to set email alerts
|

5-HT release in nucleus accumbens rescues social deficits in mouse autism model

Abstract: Dysfunction in prosocial interactions is a core symptom of autism spectrum disorder. However, the neural mechanisms that underlie sociability are poorly understood, limiting the rational development of therapies to treat social deficits. Here we show in mice that bidirectional modulation of the release of serotonin (5-HT) from dorsal raphe neurons in the nucleus accumbens bidirectionally modifies sociability. In a mouse model of a common genetic cause of autism spectrum disorder-a copy number variation on chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
144
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(160 citation statements)
references
References 47 publications
15
144
0
1
Order By: Relevance
“…Yet, evidence suggests this is not a categorical phenotype and that these data are indeed continuous. Multiple studies have now shown that typical sociability can be heightened or increased following stimulation of different pathways in the brain (Shin et al, 2018; Walsh et al, 2018). For example, optogenetic stimulation of the dorsal raphe neurons or their fibers in the nucleus accumbens increased the social preference index in WT mice (Walsh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, evidence suggests this is not a categorical phenotype and that these data are indeed continuous. Multiple studies have now shown that typical sociability can be heightened or increased following stimulation of different pathways in the brain (Shin et al, 2018; Walsh et al, 2018). For example, optogenetic stimulation of the dorsal raphe neurons or their fibers in the nucleus accumbens increased the social preference index in WT mice (Walsh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike reciprocal social interaction assays requiring manual scoring, the Social Approach Task is automated, making it ideal for mechanistic studies that require several experiments with different interventions or genetic models. For example, a recent study showed the role of dorsal raphe serotonergic connections to the nucleus accumbens in social approach behavior, and how stimulation of this pathway can correct social deficits in the 16pll.2 deletion model associated with ASD (Walsh et al, 2018). Another group showed NMDAR activation rescued social approach behavior in Shank -/- and Tbr1 +/- mutants (Lee et al, 2015; Won et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, when mice were subjected to the various mouse models, the effects of tamoxifen were apparent. Therefore, these effects should be considered when designing or conducting similar experiments …”
Section: Discussionmentioning
confidence: 99%
“…During other effort‐related behaviors (i.e., lever‐pressing tasks), serotonin neurons in the median raphe exhibited transient increases in activity and the transient signal was suggested to regulate the ventral hippocampal activities for the maintenance of effort behavior . In the NAc, optogenetic activation of serotonin axons increased social behavior of adult male mice toward juvenile male mice transiently in the order of 5 min . In the bed nucleus of the stria terminalis, the optogenetic activation of serotonin neuron enhanced freezing behavior and anxiety‐like behaviors .…”
Section: Effects Of Transient Dopamine and Serotonin On Behaviormentioning
confidence: 99%
“…42 In the NAc, optogenetic activation of serotonin axons increased social behavior of adult male mice toward juvenile male mice transiently in the order of 5 min. 43 In the bed nucleus of the stria terminalis, the optogenetic activation of serotonin neuron enhanced freezing behavior and anxiety-like behaviors. 56 Similarly, serotonin neurons projecting to the amygdala increased responses to electrical shock transiently, and their activation caused anxiety-like behavior.…”
Section: Effects Of Transient Dopamine and Serotonin On Behaviormentioning
confidence: 99%